2022
DOI: 10.13057/biodiv/d231121
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Multidrug Resistance and Methicillin-Resistant Staphylococcus aureus (MRSA) isolated from cats in Surabaya, Indonesia

Abstract: Abstract. Afnani DA, Fatih N, Effendi MH, Tyasningsih W, Kairullah AR, Kurniawan SC, Silaen OSM, Ramandianto SC, Widodo A, Hendriana K, Riwu KHP. 2022. Profile of Multidrug Resistance and Methicillin-Resistant Staphylococcus aureus (MRSA) isolated from cats in Surabaya, Indonesia. Biodiversitas 23: 5703-5709. Methicillin-Resistant Staphylococcus aureus (MRSA) is the name given to Staphylococcus aureus that has multidrug-resistance (MDR) characteristics and is resistant to ?-lactam drugs. Compared to other live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Antibiotics are administered to animals at veterinary hospitals alone, in combination with other antibiotics, or in conjunction with chemotherapeutics [ 58 ]. Extended-spectrum β-lactamase-producing E. coli is among the bacteria that are frequently discovered to be resistant to β-lactam antibiotics, aminoglycosides, TEs, and C, which are frequently used in veterinary hospitals [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are administered to animals at veterinary hospitals alone, in combination with other antibiotics, or in conjunction with chemotherapeutics [ 58 ]. Extended-spectrum β-lactamase-producing E. coli is among the bacteria that are frequently discovered to be resistant to β-lactam antibiotics, aminoglycosides, TEs, and C, which are frequently used in veterinary hospitals [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with those of Waruwu et al (2023), who discovered higher MDR S. aureus infections in cats at a rate of 19.51% (16/82). Afnani et al (2022) found a 38.89% (7/18) MDR of S. aureus in cats. This could account for the three isolates from 100 cat nose swab samples representing Surabaya's remaining low-MDR S. aureus infections.…”
Section: /14mentioning
confidence: 93%
“…It is recognized that S. aureus bacteria can spread from pets to people or vice-versa (Afnani et al, 2022). Given that pets are frequently treated as family members, it is impractical to enable physical interaction between people and animals, including skin-to-skin contact, aerosols from coughing, sneezing, and saliva (Damborg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…First, a milk sample and farmer's hand swab were taken using a loop, then spread in a zigzag manner Available at www.veterinaryworld.org/Vol.17/January-2024/25.pdf on NA media (Oxoid, UK) and incubated for 24 h at 37°C. Bacterial isolates grown on nutrient agar media were collected using a loop, streaked in a zigzag manner on mannitol salt agar (MSA) media (Oxoid), and incubated for 24 h at 37°C [27]. Suspected S. aureus colonies (golden-yellow) were further characterized using standard microbiology techniques, such as Gram staining, coagulase, catalase, β-galactosidase, pyrrolidonyl arylamidase, and acetoin production tests [28].…”
Section: Isolation and Identificationmentioning
confidence: 99%